PELATIHAN PENGENALAN AKUNTANSI BAGI UMKM DI KECAMATAN CIPAYUNG JAKARTA TIMUR - Lidya Primta Surbakti; Agus Maulana; Aniek Wijayanti; Agus Maulana (Fakultas Ekonomi Dan Bisnis Universitas Bhayangkara Jakarta Raya, 2021)
The purpose of this community service activity is to provide training to MSME actors to be able to recognize how to record their business accounting. With this accounting knowledge, MSME actors can make financial reports of their businesses. With the information presented in the financial statements, it is hoped that MSME actors can better understand how much they have to spend and how much gross profit is in their business so that they can manage and maintain the going concern of their business and can survive this pandemic. The training activities were carried out at the Cipayung sub-district office, East Jakarta. The participants are MSME business actors who are members of the Jakpreneur community, East Jakarta District. This training involved accounting lecturers from UPN Veteran Jakarta and was also assisted by students.